PERSEPSI MANFAAT DAN KEMUDAHAN PENGGUNAAN APLIKASI, EKUITAS MEREK, E-WOM TERHADAP MINAT BELI DI E-COMMERCE - Muhammad Sulton; Darianto Darianto; Elliv Hidayatul Lailiyah; Ika Purwanti (Jurnal Riset Entrepreneurship, 2023)
A total of 1,774,589 businesses from the total e-commerce business in Indonesia are still concentrated in Java. This research is a quantitative research. Sources of data used in this study are primary data and secondary data. The sampling technique used purposive sampling method. The initial stage is to produce variable data that is examined in e-commerce. Furthermore, the data is processed and analyzed, and interpreted. The benefits of this research are expected to foster business interest and increase wisdom in the use of e-commerce by knowing the goods or services being traded using the technology acceptance model approach, electronic word of mouth and brand equity in e-commerce which will ultimately lead to the development of Indonesia's digital economy which is sustainable.